Strategies for sustainable development of the power sectors of Sub-Saharan African Nations - Abubakar S. Sambo; Shehu S. Mustafa; Muhammad Mamuda (The Proceedings of the Nigerian Academy of Science)
The achievement of sustainable development goals by the Sub-Saharan Africa region depends on access to modern and efficient renewable energy technologies. The Sub-Saharan Africa Nations have been unsuccessful in fully utilizing renewable energy resources for sustainable development of the power sector. Also, developing countries in this region are susceptible to the negative health and environmental effects of fossil fuels. The goal of all countries is sustainable development of the power sector using renewable energy sources with zero greenhouse gas emissions. Though, there are a lot of problems that arise in efficient utilization of renewable energy sources in Sub-Saharan Africa. This paper studies challenges that hamper the power sector and identifies strategies for sustainable development of the power sectors in Sub-Saharan African countries. Achieving net-zero emissions is a critical cross-sector climate-action goal, yet a complex undertaking with many significant but surmountable obstacles by switching to clean energy sources, changing the way you travel, and reducing your consumption by recycling and reusing everything. In conclusion, the paper recommends the adoption of the 2050 Net Zero Agenda, local production of power plant components in Africa and the consideration of natural gas as a key transitional fuel due to its lower carbon footprint compared to other fossil fuels.